Metal-organic frameworks constructed from trivalent lanthanide nodes (Eu3+, Tb3+, and Dy3+) and thiophenethio-functionalized linker with photoluminescent response selective towards Ag+ ions. (February 2022) - Wu, Can-Min; Feng, Zihao; Zhou, Hua-Qun; Yu, Fangying; Li, Jian-Rong; Ye, Xin-He; Hu, Jieying; Chung, Lai-Hon; Liao, Wei-Ming; He, Jun
Abstract: Three metal-organic frameworks based on three lanthanide (Ln) ions (Eu 3+ for 1, Tb 3+ for 2, Dy 3+ for 3 ) and thiophenethio-functionalized linker (2, 2′, 5, 5′-tetrafluoro-3, 3′, 6, 6′-tetrakis(2-thiophenethio)-4, 4′-biphenyl dicarboxylic acid, H2 BPD-4F4TS) were prepared. Out of these MOFs, 1 demonstrated at most 8-time photoluminescence enhancement towards Ag + ions selectively. With higher quantum yield and longer excited-state lifetime after introduction of Ag + ions, the emission enhancement in 1 is rationalized as the result of strengthened 'antenna effect'. 1 represents the first example of Ln-MOFs utilizing Eu 3+ ions as nodes and thiophenethio-functionalized linkers as luminescent probes for selective Ag + -ion sensing. Graphical abstract: MOF assembled by Eu 3+ -based clusters and thiophenethio-functionalized linkers gives naked-eye observable red photoluminescence enhancement through strengthened 'antenna effect' upon introduction of Ag + ions. Image 1 Highlights: Three new photoluminescent MOFs based on Ln 3+ -nodes (Ln 3+ = Eu 3+, Tb 3+ and Dy 3+ ) and thiophenethio-functionalized linkers are reported. All three MOFs exhibit antenna effect for Ln 3+ -centered emission. Eu 3+ -analogue shows selective photoluminescence enhancement towards Ag + ions.